Supporting African Union: Do Macroeconomic Fluctuations matter? - Samba Diop; Simplice Asongu; Cheikh Tidiane Ndiaye (African Governance and Development Institute (AGDI), 2023)
In this paper, we contribute empirically to the debate on the legitimacy of the African Union by exploring the question on whether individual opinions in support of African integration are sensitive to macroeconomic fluctuations? For this purpose, we use the 4th, 5th, 6th and 8 thAfrobarometer survey data waves and a contextual logistic model. We find that an increase in GDP per capita is associated with a decline in the probability to support the African Union. Accordingly, economic growth discourages citizens' positive appraisal for the union. Our results also show an asymmetry in the relationship between public opinion on supporting the African Union and economic growth. Policy implications are discussed.
Keywords: C23; E32; O55; 330; Afrobarometer survey; African Union; Institutional support; macroeconomic fluctuations